PENGEMBANGAN DIRI DALAM ATOMIC HABITS KARYA JAMES CLEAR DAN RELEVANSINYA DALAM PENDIDIKAN AGAMA ISLAM - Nanda Inka Fitri; Jamal Fakhri; Siti Zulaikhah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of modern society, marked by rapid technological advancement and an instant culture, poses serious challenges to students’ self-development and character formation. Islamic Religious Education (Pendidikan Agama Islam/PAI) is required not only to transmit normative religious values but also to internalize them into sustainable and concrete daily habits. This article aims to examine the concept of self-development in Atomic Habits by James Clear and analyze its relevance to Islamic Religious Education. This study employs a qualitative approach using library research. The primary data source is the book Atomic Habits, supported by scientific literature related to self-development, habit psychology, and Islamic education. Data analysis is conducted through content analysis and a descriptive-interpretative approach. The findings indicate that the concept of atomic habits, which emphasizes small and consistent changes, strongly aligns with Islamic principles such as istiqāmah (consistency), intention (niyyah), and the habituation of righteous deeds. The principles of habit formation proposed in Atomic Habits are relevant to be integrated into Islamic Religious Education as a strategy to gradually and sustainably develop students’ Islamic habits. This study concludes that integrating the Atomic Habits concept into Islamic Religious Education has the potential to strengthen character formation, discipline, and students’ self-development in facing the challenges of the modern era.